Methodical approaches to the determination of readiness of introduction of «blue ocean» strategy on the enterprises of food industry - Belova, Tatyana; Krainiuchenko (Fornolyak), Olga; Rozumey, Svitlana; Petukhova, Olga (My University, 2020)
In the conditions of competition improvement there is a necessity to find new decisions in relation to the development and strategies that will be able to provide proof market positions. One of such decisions is the conception of market space creation free from competition − so-called "blue ocean". However, there is a large variety of open questions of practical realization of the marked conception. Accordingly, the aim of the research is the development of suggestions in relation to the choice of optimal way of "blue ocean" strategy forming. To achieve the aim of the article, firstly, the factors that are the pre-condition for transition from existed market space to new one were outlined, and, secondly, methodical recommendations in the relation to realization of "blue ocean" strategy were designed. Offered approaches envisage the evaluation of strategic position of industry/company by establishment and quantitative measuring of factors, that have positive and negative influence (named, accordingly, by success and challenges), and also the research of company’s tuning degree to perception of "blue ocean" strategy. To find out the strategic position of industry/company the recommended matrix "success – challenges", that helps to envisage actions in direction of motion to blue space. The designed methodical approaches were approved on the example of Public joint stock company "Obolon". Introduction of the offered recommendations in relation to realization of "blue ocean" conception will promote the search of new strategic decisions which help companies to develop the unique market space.
Keywords: development; розвиток; Red Ocean; Червоний океан; Blue Ocean; Блакитний океан; matrix Success – Challenges; матриця Успіх – виклики; Blue Ocean strategy; стратегія Блакитний океан; кафедра маркетингу